Treatment Adherence Among Persons Receiving Concurrent Multidrug-Resistant Tuberculosis and HIV Treatment in KwaZulu-Natal, South Africa - Stephens, Fay; Gandhi, Neel R; Brust, James C M; Mlisana, Koleka; Moodley, Pravi; Allana, Salim; Campbell, Angie; Shah, Sarita (Journal of acquired immune deficiency syndromes (1999), 2019)
Success in multidrug-resistant tuberculosis (MDR-TB) and HIV treatment requires high medication adherence despite high pill burdens, frequent adverse events, and long treatment duration, which may jeopardize adherence. We prospectively compared MDR-TB/HIV-coinfected persons to those with MDR-TB alone to determine the impact of concurrent treatment on adherence and outcomes. We assessed medication adherence monthly using 3-day recall, 30-day recall, and visual analog scale and examined adherence to monthly study visits (months 0-12). We determined the proportion of participants fully adherent (no reported missed doses) to MDR-TB vs. HIV treatment by each measure. We assessed the association of medication and clinic visit adherence with MDR-TB treatment success (cure or completion, 18-24 months) and HIV virologic suppression. Among 200 patients with MDR-TB, 63% were women, median age was 33 years, 144 (72%) were HIV-infected, and 81% were receiving antiretroviral therapy (ART) at baseline. Adherence to medications (81%-98% fully adherent across all measures) and clinic visits (80% missed ≤1 visit) was high, irrespective of HIV status. Adherence to ART was significantly higher than to MDR-TB treatment by all self-reported measures (3-day recall: 92% vs. 84%, respectively; P = 0.003). In multivariable analysis, the adjusted risk ratio of unsuccessful MDR-TB treatment increased with every missed visit: 1.50, 2.25, and 3.37 for unsuccessful treatment, for 1, 2, and ≥3 missed visits. Adherence to ART was higher than to MDR-TB treatment among persons with MDR-TB/HIV coinfection. Missed clinic visits may be a simple measure for identifying patients at risk of unsuccessful MDR-TB treatment outcome.